Program-Program dalam Mengatasi Child Trafficking : Literatur Review - Agra Asmaldha; Adelia Yasmin; Adelia Dwi Rizki; Ade Fitri Fauziah; Dinita Anggun Prasetyati; Elda Mariyani; Erika Dayanti; Farida Aeni; Fardilla Rochman Utami; Fransiska Oktaviani; Fadiyah Hurryos; Khalisah Amalia; Faricha Ramadhania; Hanna Nurul Irbah; Fahriza Srihartantri; Renta Sianturi (AKPER Pasar Rebo, 2022)
Child trafficking as the social issues in the form of crimes against humanity, violations of human rights, and degrading human dignity, especially children. Trafficking victims in general are children and underage women where the victims are those who experience difficulties in the economic field. Purpose: this article aims to find out the child protection program for victim of child trafficking. Methods: this article was written using a literature review approach, article searches from Google Scholar got 7 articles, Science Direct got 1 articles, Neliti got 2 articles. Articles in the last year (2011-2021). Results: from the literature that we have reviewed, there are programs implemented by either the government or institutions in dealing with child trafficking, in this case they have been implemented and show changes in dealing with child trafficking victims. Conclusion: there are several programs that have been implemented to deal with children with trafficking victims, including preventing, protecting, and saving children from the crime of selling children.